2002
DOI: 10.1017/s1047951102000884
|View full text |Cite
|
Sign up to set email alerts
|

“Bail-out” stenting for acute obstruction of a modified Blalock-Taussig shunt following selective angiography

Abstract: A 3-year-old boy developed acute obstruction of a left modified Blalock-Taussig shunt following selective power injection of contrast in the shunt. Balloon dilation was ineffective due to rapid recoil of the narrowed segment, but implantation of a stent effectively abolished the obstruction. The obstruction itself may have been produced by an intimal flap caused by the power injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Additionally, this study demonstrated that only one out of seven failed cases received stent insertion, while the other 6 cases underwent angioplasty without stenting ( 35 ). Evidence of restenosis can be found on different imaging modalities assessments several years after the first intervention and may need re-stenting ( 19 , 66 ). Another study reported that transcatheter procedures in 23 BTSs were successful and effective in 96% of cases ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this study demonstrated that only one out of seven failed cases received stent insertion, while the other 6 cases underwent angioplasty without stenting ( 35 ). Evidence of restenosis can be found on different imaging modalities assessments several years after the first intervention and may need re-stenting ( 19 , 66 ). Another study reported that transcatheter procedures in 23 BTSs were successful and effective in 96% of cases ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant therapy could be considered in cases with thrombotic or in subjects at high risk for thrombotic events. Heparin was given before stenting for all patients with close monitoring of activated clotting time around 200 s ( 66 , 95 ). Post-procedure, continuous intravenous heparin infusion was given and was followed by oral aspirin ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients that develop graft obstruction, the risk of surgery versus catheter intervention must be weighed. Literature to date has reported the risks of shunt revision | 77 [2][3][4] and the feasibility of percutaneous graft stenting [1,3,[11][12][13][14][15][16][17][18] and overdilation [19][20][21][22]. This single-center cohort study now contributes a large experience of stent interventions and overdilation practice for small Gore-Tex ® grafts over a range of indications: addressing safety, technical results, and long-term clinical impact.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon angioplasty to treat acutely stenosed shunts and conduits has been reported since the 1990s [5][6][7][8][9][10]. This was rapidly replaced by stent implantation (due to safety concerns), described in case reports and small series [1,[11][12][13][14][15][16][17][18]. Of late, graft stenting has emerged as an important interstage intervention [19], particularly in centers utilizing the Sano modification to classical Norwood [1,3,11].…”
Section: Introductionmentioning
confidence: 99%